2003
DOI: 10.1017/s0952523803201012
|View full text |Cite
|
Sign up to set email alerts
|

Center-surround organization in bipolar cells: Symmetry for opposing contrasts

Abstract: Intracellular recordings were obtained from 73 cone-driven bipolar cells in the light-adapted retina of the tiger salamander (Ambystoma tigrinum). Responses to flashes of negative and positive contrast for centered spots and concentric annuli of optimum spatial dimensions were analyzed as a function of contrast magnitude. For both depolarizing and hyperpolarizing bipolar cells, it was found that remarkably similar responses were observed for the center and surround when comparisons were made between responses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(57 citation statements)
references
References 30 publications
7
47
1
2
Order By: Relevance
“…We found that the response of the surround was delayed by about 50 ms with respect to that of the receptive field center, a finding consistent with the common view that the surround response is mediated by slower mechanisms than that of the center. The cone voltage showed no evidence for center-surround antagonism (Fahey & Burkhardt, 2003) in agreement with Hare and Owen (1992). This finding is compatible with the view that surround antagonism is due to modulation of calcium currents in the cone pedicle due to feedback from horizontal cells and is not normally detectable in the cone photovoltage Thoreson et al, 2008) .…”
Section: Center-surround Organizationsupporting
confidence: 88%
See 1 more Smart Citation
“…We found that the response of the surround was delayed by about 50 ms with respect to that of the receptive field center, a finding consistent with the common view that the surround response is mediated by slower mechanisms than that of the center. The cone voltage showed no evidence for center-surround antagonism (Fahey & Burkhardt, 2003) in agreement with Hare and Owen (1992). This finding is compatible with the view that surround antagonism is due to modulation of calcium currents in the cone pedicle due to feedback from horizontal cells and is not normally detectable in the cone photovoltage Thoreson et al, 2008) .…”
Section: Center-surround Organizationsupporting
confidence: 88%
“…We believe that our work (Fahey & Burkhardt, 2003) is the first to systematically investigate the full contrastresponse curves for both negative and positive contrasts for both center and surround. In our sample, the size of the center ranged from about 100-500 lm in diameter across the bipolar population in both ON and OFF bipolars (see also Hare & Owen, 1990;Zhang & Wu, 2009).…”
Section: Center-surround Organizationmentioning
confidence: 98%
“…The ineffectiveness of the GABA antagonists to eliminate the surround responses of the OFF bipolar cells in these experiments may be due to inappropriate light adaptation conditions. The retina has been maintained under mid to high scotopic illumination conditions, while the bipolar cell surround responses are strongest under light adapted conditions [207, 208]. To reveal the role of the GABAergic system in the centre-surround organization of cone ON and OFF bipolar cells, the effects of GABA receptor antagonists should be determined under maintained light adapted conditions.…”
Section: Effects Of Gaba On Bipolar Cellsmentioning
confidence: 99%
“…First, following maintained (30 min) bright background illumination, stimulation of the RF surround alone using an annulus or ring of light produces a response that is opposite in polarity to that produced by center (spot) stimulation alone, a phenomenon called “surround activation,” and surround stimulation in the presence of center stimulation using spot and annulus together reduces the amplitude of the center response, a phenomenon called “surround antagonism” [18]. Second, although cBC and GC surround responses are strongest under maintained bright background illumination, surround strength progressively decreases as the light level decreases so that the surround is minimal following maintained darkness [712]. This adaptive process likely contributes to modulation of the spatial discrimination ability of human and monkey observers by the ambient light level [13].…”
Section: Introductionmentioning
confidence: 99%